Thailand : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This Selected Issues report on Thailand discusses the rapid growth years of the country before and after the 1997 balance-of-payments crisis. The report discusses development of the crisis and the steps taken to normalize the situation; credit growth before and after the crisis; public debt dynamics in the aftermath of the crisis; export performance before and after the crisis; and an analysis of the role of fiscal policy that led to the 1997 crisis. The report also highlights weaknesses that were threatening the sustainability of Thailand's economic growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet